Model Seleksi Pegawai di PT. Telekomunikasi Indonesia, tbk - Ilyas, Anita (Jurnal Wacana Kinerja: Kajian Praktis-Akademis Kinerja dan Administrasi Pelayanan Publik, 2010)
The succes achieved by PT. Telkomunikasi Indonesia Tbk (TELKOM) as one of the national company, is not an easy thing. Business strategy human resources management competency-based, as it positions as an asset of the human resources organiztaion is managed and maintained their competence with a very serious and sustained effort that occurs starting from recruitment & selection, training & development, performance appraisal, compessation & benefits to career developmentnya. In career development is done through a career with the selection method through the following phases.